Odpowiedzi

2009-12-14T17:16:33+01:00
3x-y=5/*2
5x-2y=7

6X-2Y=10
5x-2y=7
odejmujemy od 1 równania 2 izostaje
x=3
y=3x-5
y=-4 a x=3

B x-3y=5/*3
y+3x=-5

3x-9y=15
3x+y=-5 odejmujemy od 1 równania 2
-10y=20
y=-2
x=3y+5
x=-1 y=-2
Najlepsza Odpowiedź!
2009-12-14T17:19:29+01:00
A)
5=3x-y
5x-2y=7

y=3x-5
5x-2(3x-5)=7

y=3x-5
5x-6x+10=7

y=3x-5
-x=-3

y=3*3-5
x=3

y=4
x=3

b)
x-3y=5
y+3x=-5

x=3y+5
y+3(3y+5)=-5

x=3y+5
y+9y+15=-5

x=3y+5
10y=-20

x=3*(-2)+5
y=-2

x=-1
y=-2
2009-12-14T17:23:23+01:00
A)5=3x-y
5x-2y=7

5=3x-y
7=5x-2y

5=3x-y/×(-2)
7=5x-2y

-10=-6x+2y
7=5x-2y

-3=-1x
5=3x-y

x=3
5=3×3-y

x=3
5=6-y

x=3
y=6-5

x=3
y=1


b) x-3y=5
y+3x=-5

x-3y=5/× (-3)
3x+y=-5

-3x+6y=-15
3x-y=-5

5y=-20/:5
3x+y=-5

y=-4
3x-4=-5

y=-4
3x=-5+4

y=-4
x=3